Neutron scattering and transport propierties in liquid H2 and D2 using a synthetic scattering function - Granada, José Rolando (Comisión Nacional de Energía Atómica; Argentina, 1988)
Fil: Granada, José Rolando Comisión Nacional de Energía Atómica; Argentina